'Heliosphere': Intensities, the ionosphere and the solar wind. Issue 2 (1st September 2013) - Grant, Jane
This article will describe two forthcoming art/science projects, 'Heliosphere' (Grant,  Kin, Matthias) and 'The Sun Project' (Grant, Kin, Matthias). Each project materializes data from solar flare activity by tracking the solar wind across the Earth.Using information streamed from satellites orbiting the Earth's atmosphere and from terrestrial detectors, the Sun's activity will be visualized and sonified at sites across the Earth. The article also describes the research context undertaken in developing the work including solar physics, anthropology the history of science.